ความสัมพันธ์ระหว่างการกระจายรายได้กับการเจริญเติบโตทางเศรษฐกิจของประเทศไทยรายภูมิภาค - สุมิตรา สุขสำราญ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The purpose of this study is to investigate the relationship between income distribution and economic growth of Thailand by regions using panel data. The economic variables in the study include Gross Regional Product (GRP) and Gini coefficient. The secondary data used covers the period of 1996 to 2013. Econometric techniques used for analysis were panel unit root ,panel cointegration ,and estimate equation using Ordinary Least Squares(OLS). According to the unit root, the variables are stationary at the 1st difference. Then ,the Panel Cointegration test examined the long run relationship and found that Gross Regional Product and Gini coefficient is significant if Gini coefficient is identical. In addition, Gini coefficient has a negative relationship with economic growth.